The Position of Visum Et Reperertum in Proving the Crime of Sexual Violence - Teuku Heri Hermawan; T. Riza Zarzani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The examination of a criminal case in a judicial process essentially aims to seek material truth, namely the complete truth of a criminal case by applying the provisions of criminal procedure law in an honest and timely manner with the aim of finding out who is the criminal who can be charged with committing an offense. The making of visum et repertum gives full duty to the doctor as the executor in the field to assist the prosecutor in determining the direction of the indictment that will be charged against the defendant, as well as assisting the judge in finding material truth in deciding a criminal case. The approach used in the research is a normative juridical approach. The juridical-normative approach The data source of a research is primary data and secondary data. Because this research is normative legal research, the sources studied are secondary data sources. Qualitative analysis is carried out by describing quality data in the form of sentences that are regular, sequential, logical, not overlapping, and effective. The role of Visum et Repertum in assisting the examination process of a case is not only useful for investigators to uncover the criminal offense, but also useful for examination in the trial of the case. Visum et Repertum as stated in Article 184 paragraph (1) KUHAP point c is a valid evidence. This makes the Visum et Repertum legally binding in assisting the resolution of a case. Visum et Repertum in the investigation process of a criminal act of rape aims to support investigators in tracking and collecting evidence in addition to other evidence such as victim testimony, suspect testimony, witness testimony and examination of other evidence. It is necessary for investigators to have additional knowledge about medical terms in a Visum et Repertum. This knowledge is useful so that investigators do not misinterpret the results of the Visum et Repertum obtained so that it can influence and determine the actions taken by investigators in solving a case.